Hybrid wind-wave systems: The case of the VolturnUS-S semi-submersible platform (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Wind-wave hybrid floating systems are subject to active research and development in academia and industry. Industrialization of hybrid wind-wave energy systems will benefit from modular designs, allowing floating platforms to be used with or without wave energy converters (WECs). This work explores the design process to use oscillating water column (OWC) WECs as modular add-on features to existing semi-submersible floating platform designs. As the base case design, the IEA 15 MW offshore reference wind turbine with the VolturnUS-S floating platform designed by the University of Maine was used. A design approach was proposed, which involved various tools, such as OpenFAST developed by NREL, and the OWC Modelica tool developed at IST/ULisboa. Aero-hydro-servo-elastic simulations were performed to analyze the influence of the wind turbine energy generation design modifications and damage equivalent loads (DELs). The hybrid platform was modeled in the OWC Modelica tool to assess the wave energy conversion and the interaction between OWCs and the floating platform. The investigated hybrid design did not significantly increase DELs of the wind turbine in aero-hydro-servo-elastic simulations. The hybrid system does not decrease the LCOEcompared to a standalone floating wind turbine. The main cost driver was identified to be the material of the OWCs' ducts. Furthermore, the coupling forces between OWCs and the floating platform were found to be in the same order of magnitude as the wave excitation and radiation forces. The  possibilities of including these forces in OpenFAST and the challenges for this are discussed.